PENGGUNAAN DIKSI DALAM CERITA FANTASI SISWA SMP NEGERI 12 PONTIANAK - Wulandari, Kinanti; Sulissusiawan, Ahadi; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractDictation is the right and harmonious choice of words to express ideas. Mistakes in using diction often occur especially in the writing aspect. Misuse of diction causes the real meaning not conveyed properly. The problem in this study is "How do you use diction in the fantasy stories of VII grade students of SMP Negeri 12 Pontianak?" The results of this study are useful as a contribution to thinking in a set of theories relating to the use of diction in fantasy stories. The method used in this research is descriptive method with a qualitative research form. The source of the data in this study was the seventh grade students of SMP Negeri 12 Pontianak, amounting to 35 people. The technique used in this study is an indirect technique in the form of a test technique. Data collection tools in this study are researchers as key instruments, stationery, paper, laptops, and tests. Based on research that has been found 26 errors in the use of diction. The data is obtained from the data source used. The results of analyzing the use of diction data, found 13 errors in the accuracy of the use of diction, 10 errors in the suitability of the use of diction, and 3 errors in the prevalence of diction usage.Keywords: Fantasy Stories, Diction, Narration, Students.